Co-existence of ischemic stroke in Rheumatic and non-rheumatic atrial Fibrillation in a tertiary care teaching hospital of Western Nepal - Kafle, Ram Chandra; Jha, Girija Shankar; Paudel, Navaraj; Alurkar, Vijay Madhav (Journal of College of Medical Sciences-Nepal, 2017)
Background & Objectives: Stroke is a major public health burden worldwide leading to long-term morbidity and even mortality. Atrial fibrillation (AF) is the most common sustained arrhythmia and is an independent factor to increase risk of ischemic stroke. The risk of stroke further enhanced in rheumatic atrial fibrillation and affects younger population of developing countries. The study has aimed to find out frequency of co-existence of stroke in AF and secondarily to look for age distribution of stroke and risk factors of AF. Materials & Methods: A retrospective analysis of trans-thoracic echocardiographic records of patients from 1st June 2009 to 31st June 2016 was done. Data were collected in a pre-structured proforma and analyzed. Results: Among 15767 echocardiographies, 577 (3.65%) cases were recorded to have atrial fibrillation. Mean age 65(±15) years ranging from 14 to 100 years. Rheumatic heart disease was the second most common cause of atrial fibrillation after hypertension. The co-existence of ischemic stroke was seen in 87(15.07%) cases with male to female ratio of 1:1.3. The proportion of stroke in rheumatic Atrial fibrillation was 21(18.75%) which was higher than in non-Rheumatic atrial fibrillation 66(14.2%). Conclusion: Rheumatic heart disease is contributing as second most common cause of atrial fibrillation after hypertension, nearly one fourth of total stroke and most common (93%) cause of stroke below the age of 45 years. Preventive strategies aimed at health awareness about rheumatic fever, screening programs at community level, early detection and treatment for hypertension and Rheumatic heart disease can contribute in reduction of stroke burden.